The effect of a self-etching primer on the shear bond strength of orthodontic brackets - Tuano, Cecile Ammeli P.
Abstract:The purpose of this study was to determine the effects of a bonding system with a self-etching primer on the shear bond strength and bond failure mode of orthodontic brackets. Bovine lower incisors were extracted from mandibles of cows that were slaughtered several hours prior to the extraction procedure. Sixty teeth were stored in individual bottles containing distilled water at room temperature 9 days prior to the start of the bonding procedure. Universal upper central Mini Uni-Twin Brackets (3M Unitek, Monrovia, California) with 0 torque and 0 angulation were then bonded to the teeth using either one of two protocols: the control group, System 1+ (Ormco, Orange, California), and the experimental group, Transbond XT with Transbond Plus Self-Etching Primer (3M Unitek, Monrovia, California). All the teeth were placed in a humidor at 37%C for 48 hours. The shear bond strength (SBS) was tested using a universal testing machine (Instron) with a crosshead speed of 1 cm/min with the jig on upper jaw of the Instron parallel to the facial surface of the tooth. Immediately after debonding, the amount of composite remaining on the tooth was assessed using the Adhesive Remnant Indes (ARI). The result of the paired t-test indicate that the mean SBS of the control and experimental groups are significantly different )p=0.05). The mean SBS of Transbond XT with Transbond Plus Self-Etching Primer was significantly lower (= 16.10  3.51 MPa) than the mean SBS of System 1+ (= 19.07  6.86 MPa). The results of the Wilcoxon Signed-Ranks Test Indicate that the System 1+ is associated with higher ARI scores (less residual adhesive on the tooth) compared to Transbond XT with Transbond Plus Self-Etching Primer (p=0.001). Since the experimental group has a mean shear bond strength that is higher than what is clinically acceptable and has a desirable bond failures after debonding, Transbond XT with Transbond Plus Self-Etching Primer can be recommended for use in bonding orthodontic brackets.